Penggunaan Media Power Point Dalam Proses Pembelajaran Pendidikan Agama Islam Kelas V Di SDN 21 Gantung Ciri Solok - Lusi Putri Handayani; Salmiwati Salmiwati; Jnnaidi Jnnaidi; Yelfi Dewi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The researcher conducted research at SDN 21 Gantung Ciri Solok which was motivated by the way the use of power point media was not optimal which was carried out by Islamic Religious Education teachers, Islamic Religious Education teachers could not use power point as they should, teachers used power point as well as copying the contents of the book are like ants swarming and this makes students not interested in learning to use power point media. This study aims to find out how teachers create and use power point media and what obstacles Islamic Religious Education teachers face in using power point for class V at SDN 21 Gantung Ciri Solok. descriptive qualitative research method aimed at describing and analyzing phenomena and events, social activities, attitudes, beliefs, thoughts of people individually and in groups with the type of field research (field research). Data collection was carried out using observation techniques, interviews, and also documentation. The key informants in this study were fifth grade Islamic Religious Education teachers at SDN 21 Gantung Ciri Solok.